Diagnosis By Ultrasound Of The Chorionicity And Amnionicity In The Multiple Pregnancy - Gil-Guevara, Enrique Damián (2019)
Determination of the chorionicity and amnionicity by ultrasound is the most important step in the management of the multiple pregnancies. This diagnosis should be done in the first trimestre of the pregnancy, not only because of a less difficult process but also because it constitutes the beginning of several steps to follow in the control of these types of pregnancies. All this makes highly necessary that professionals dealing with this kind of ultrasounds have the right knowledge to assess correctly and promptly the chorionicity and amnionicity in multiple pregnancies.